2013
DOI: 10.1242/jeb.088898
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms of the widespread production of phosphorylated HSP25 after fatiguing muscle stimulation

Abstract: Summary We already showed a widespread heat shock protein (HSP) response to fatigue of a single hindlimb muscle, responsible for a global adaptive response to an acute localized stress. We also demonstrated that the HSP response resulted from the activation of nerve afferents from the stimulated muscle. However, we did not examine the role played by the different muscle afferents as well as the efferent arm of HSP response. We here measured the changes in phosphorylated HSP25 (pHSP25) levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…As already suggested 7 , a downregulation of HSP production in some individuals could be caused by the repetition of exercise bouts at high energetic levels. As cited above, the activation of the group III or IV muscle afferents triggers the HSP production in working and resting muscles as well as in the brain and different organs 17 . It may be hypothesized that the prolonged activation of these muscle afferents by the oxidative stress could induce a reduction of HSP production in patients with ME/CFS.…”
Section: Biological Events Accompanying the Electrophysiological Disomentioning
confidence: 87%
See 1 more Smart Citation
“…As already suggested 7 , a downregulation of HSP production in some individuals could be caused by the repetition of exercise bouts at high energetic levels. As cited above, the activation of the group III or IV muscle afferents triggers the HSP production in working and resting muscles as well as in the brain and different organs 17 . It may be hypothesized that the prolonged activation of these muscle afferents by the oxidative stress could induce a reduction of HSP production in patients with ME/CFS.…”
Section: Biological Events Accompanying the Electrophysiological Disomentioning
confidence: 87%
“…Multiple stressors, such as fatiguing muscle contraction, muscle acidosis, hypoxia, ischemia, and ROS, stimulate these muscle afferents 1416 . Their activation by muscle fatigue triggers the widespread production of HSPs 17 .…”
Section: The General Mechanisms Of Muscle Fatiguementioning
confidence: 99%
“… 55 Interestingly, Jammes et al have reported that a widespread HSP25 response to fatigue in a single hindlimb muscle is responsible for a global adaptive response to acute localized stress and have demonstrated that group III and IV muscle afferents play an important role in the fatigue-induced p-HSP25 response; moreover, the sympathetic nerve supply to the muscles and kidney comprises the efferent arm of the p-HSP25 activation. 56 Skeletal muscle HSP25 has been reported to stabilize muscle structure and repair damaged muscle proteins, 57 as well as to decreases apoptosis in cultured muscle C2C12 cells by inhibiting the intrinsic and extrinsic apoptotic cell death pathway. 58 …”
Section: Factors That Affect Muscle Contraction and Fatiguementioning
confidence: 99%
“…When muscle afferents are triggered by muscle fatigue, this triggers the production of heat shock proteins (HSPs) ( 299 ). HSPs protect muscle cells against any deleterious effects of ROS generated during exercise by activation of antioxidants ( 300 , 301 ).…”
Section: Redox Imbalance and Oxidative Stressmentioning
confidence: 99%